감잎의 광노화 피부 개선에 미치는 효과(2) - 이창현(Chang Hyun Lee); 김남석(Nam Seok Kim); 최동성(Dong Seong Choi); 오미진(Mi Jin Oh); 마상용(Sang Yong Ma); 김명순(Myoung Soon Kim); 유승정(Seung Jeong Ryu); 권진(Jin Kwon); 신현종(Hyun Jong Shin); 오찬호(Chan Ho Oh) (동의생리병리학회지, 2014)
This study was performed to investigate the anti-photoaging effects of Persimmon leaf tea(PLT) in hairless mice(SKH-1) exposed to UVB radiation. The animals were divided into non-treated group (normal, N) and UV-radiated groups. UV-radiated groups were divided into only UV-radiated group(control, C) and UV-radiated and PLT treated experimental groups[first extraction treated group(PLT-I), second extraction treated groupe(PLT-II), and third extraction treated group(PLT-III)]. Three PLT treated experimental groups of mice were treated with both oral administration(300mg/Kg B.W./day) and topical application (100 ul of 2% conc./mouse/day) for 4 weeks. Anti-photoaging effects of Persimmon leaf were evaluated by MTT assay, anti oxidative reaction, MMP immunohistochemistry, gelatin zymography assay and RT-PCR observations. Treatment with Persimmon leaf tea(PLT)-I, and -III groups decreased immunohistochemical density of matrix metalloproteinases(MMP)-3 and -9 related to degradation of extracellular matrix in skin. Especially, immunohistochemical density of MMP-2 decreased in PLT-I, -II and -III groups in skin. On the effects of antioxidant function on the treatment with Persimmon leaf tea(PLT), treatment of HaCaT cells with extracts of PLT-I and PLT-II had also significantly reduced intracellular ROS produced by UVB irradiation in a dose dependent manner(PLT-I, p<0.05, p<0.01, p<0.001; PLT-II, p<0.01, p<0.001). Gelatin zymography assay revealed that PLT-II and PLT-III (200 ug/ml) had inhibitory effect on MMP-9 expression in UVB-radiated HaCaT cells. Western blot analysis revealed that PLT-1, -II and -III groups down-regulates the expression of inflammatory associated genes(IL-$1β$) and PLT-1 and -II groups down-regulates the expression of TNF-${α}$ in a dose dependent manner. Our study suggests that Persimmon leaf tea(PLT) extracts participates in inhibitory effects on the morphological and molecular experiments related to photoaging skin on UVB irradiated hairless mice.